Teaching Principals in Small Rural Schools: “My Cup Overfloweth” - Wallin, Dawn C.; Newton, Paul (Alberta Journal of Educational Research, 2015)
This paper presents the results of interviews with 12 Manitoba and Alberta rural teaching principals regarding their leadership practices in small schools. The overwhelming theme mentioned by these teaching principals was the joy and sense of purpose they found in the relationships they cultivated with children, staff, and community members because of the ‘advantages’ they had working in small schools. The paper details the small schools context within which teaching principals are working in these two provinces and outlines the role of reciprocal relationality that is central to their leadership efforts in small rural schools. Cet article présente les résultats d’entrevues auprès de douze directeurs-enseignants d’écoles rurales au Manitoba et en Alberta portant sur les pratiques de leadership dans les petites écoles. Le thème dominant qui en est ressorti est celui de la joie et le sentiment d’un but à atteindre qu’ils retiraient des rapports entretenus avec les enfants, le personnel et les membres de la communauté et qu’ils associaient aux « bienfaits » de travailler dans une petite école. L’article décrit en détail le contexte scolaire dans lequel travaillent les directeurs-enseignants dans ces deux provinces, et dresse un portrait du rôle de la relationnalité réciproque qui est au centre de leurs efforts comme dirigeants de petites écoles en milieu rural.